2022
DOI: 10.3390/cells11162563
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Platelets: Lower G12/13 Expression Contributes to Reduced Secretion of Dense Granules

Abstract: Despite fully functional primary hemostasis, platelets of healthy neonates exhibit hypoaggregability and secretion defects, which may be adaptations to specific requirements in this developmental stage. The etiologies for reduced signal transduction vary with the type of agonist. The discovered peculiarities are lower receptor densities, reduced calcium mobilization, and functional impairments of G proteins. Reduced secretion of dense granules has been attributed to lower numbers of granules. Signaling studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“… 31 , 33 , 34 , 35 More recent studies have shown distinct platelet hyporeactivity upon immunoreceptor and GPCR stimulation 36 , 37 and have discussed reduced G 12 /G 13 expression as a causative factor for reduced δ-granule secretion. 38 These controversial findings could be explained by the heterogeneous study design regarding readouts (granule release, GPIIb/IIIa activation, aggregometry, and electron microscopy), the material used (peripheral vs umbilical blood), time points, or the respective control group (adults vs infants). Comprehensive studies comprising a continuum of preterm and term neonates or numerous agonists and activation markers are still very rare, owing to limited biomaterial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 , 33 , 34 , 35 More recent studies have shown distinct platelet hyporeactivity upon immunoreceptor and GPCR stimulation 36 , 37 and have discussed reduced G 12 /G 13 expression as a causative factor for reduced δ-granule secretion. 38 These controversial findings could be explained by the heterogeneous study design regarding readouts (granule release, GPIIb/IIIa activation, aggregometry, and electron microscopy), the material used (peripheral vs umbilical blood), time points, or the respective control group (adults vs infants). Comprehensive studies comprising a continuum of preterm and term neonates or numerous agonists and activation markers are still very rare, owing to limited biomaterial.…”
Section: Discussionmentioning
confidence: 99%
“… 34 In addition, altered expression of G protein subunits G α12/13 and G αi2 might interfere with the responsiveness to classical agonists such as collagen or thrombin, leading to an increased basal cAMP level in neonatal platelets, which might contribute to a “hyporesponsive” platelet phenotype. 38 The diminished response to TRAP-6 might also be a consequence of the reduced expression; a future study might elaborate on thrombin responsiveness with more concentrations and including a PAR4 peptide. (4) Because of the limited blood samples available from preterm and term neonates, we decided to select concentrations according to the current (inter)national guidelines.…”
Section: Discussionmentioning
confidence: 99%